PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PENGGUNA VIVO SMARTPHONE DI KOTA BATAM - Simanjuntak, Nur Annisa; Tampubolon, Rikson Pandapotan (LPPM Universitas Putera Batam, 2019)
The use of smartphone based on the operating system in Indonesia is controlled by Android. In November 2018 the Statista survey institute reported that the use of operating systems in Indonesia was dominated by Android. As many as 72.84% of smartphone users use the Android operating system, and IOS gets user numbers of 4.34% of total users in Indonesia. The method used in this study is the method of multiple linear regression analysis. The research design used was descriptive analysis. Tests carried out consisted of validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination, t-test, and f-test. The population in this study was Smartphone Vivo users in Bengkong District with a total sample of 274 people. The results showed that the price variable have a positive and significant effect on Vivo Smartphone customer satisfaction. Product quality variables have a positive and significant effect on user satisfaction of Vivo smartphones. Product quality and price variables have a positive and significant effect on user satisfaction of Vivo Smartphone.